The Implementation of Law Enforcement on Environmental Crime Perpetrated by Corporations in Relation to River Pollution - Silaban, Rudolf (Faculty of Law, Universitas Pekalongan, 2024)
There is an increasing trend to criminalize companies committing environmental crimes through criminal policies. Law No. 32 of 2009 on Environmental Protection and Management considers companies as legal entities with criminal liability. However, in practice, there are many obstacles in enforcing the law against businesses that commit criminal acts. For example, no company has been sanctioned for pollution cases in river basin areas (DAS). This research focuses on examining issues related to the application of environmental criminal liability by companies under Indonesian law and the efforts to tackle environmental crimes committed by companies. The research method used in this study is normative jurisprudence. According to the implementation of the law, companies that commit crimes of polluting river basins can be held criminally liable, including sanctions, fines for the company, and the directors or managers of the company being subject to corporate criminal penalties. To effectively address environmental crimes committed by companies around the river basins, two approaches can be used: first, criminal action (punishment) and second, collective action, which is a combination of non-criminal and criminal practices.